COMPETENCE-BASED APPROACH WHILE TEACHING FUNDAMENTAL SCIENCE SUBJECTS AT MEDICAL UNIVERSITY - V. Y. Gelman; N. M. Khmelnitskaya (Russian State Vocational Pedagogical University, 2016)
The aim of the study is to analyze the features of the competence approach application in the theoretical and natural science subjects' teaching in medical school.Methods. The method of expert estimation is used in order to find out main tendencies and problems arising in the course of professional competencies development. The implementation of problem-oriented method in fundamental disciplines' teaching is applied.Results. The effect of the competence approach on educational process is shown in the teaching experience of pathological anatomy and statistics. The problems and complicating factors faced by teacher are identified. The basic approaches facilitating the development of professional competencies based on a fixed time allotted for studying a particular discipline are proposed.Scientific novelty and practical significance. The proposed approaches and practical recommendations will enable to form more efficiently the competences in fundamental disciplines. The implementation of competence approach in teaching the fundamental science subjects requires adjustments of substantial and methodological levels of training including the active use of information technologies and a substantial increase in the role of seminars and self-studies. The advantage of the proposed approaches concludes in their universality: with some adjustment, they can be used in teaching other subjects, regardless of the specifics and the type of educational institution.